2013
DOI: 10.4187/respcare.02780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Airway Wall Thickness Via High-Resolution Computed Tomography in Mild Intermittent Asthma

Abstract: INTRODUCTION:This study aims to evaluate bronchial thickness via thorax high-resolution computed tomography (HRCT) in subjects with mild intermittent asthma in comparison with healthy control subjects. METHODS: A total of 37 out-patients (mean ؎ SD age ‫؍‬ 36.7 years (9.7 years); 54.8% males) with mild intermittent asthma and 13 healthy control subjects (mean ؎ SD age ‫؍‬ 25.0 years (2.9 years); 61.5% males) were included in this case control study. , P ‫؍‬ .046) were significantly higher in subjects than cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“… 34 It was proposed that leptin which is one of the best-known systemically secreted adipokines would affect proliferation and survival of eosinophils and promote airway inflammation in several reports. 35 36 37 Considering that there were reports describing airway inflammation in asthma could be demonstrated as bronchial wall thickening on CT, 38 39 the positive association of SFA with WA or TA shown in this study might suggest that subcutaneous fat tissue may influence the airway inflammation through systemically secreted adipokines. These results were unexpected because visceral fat was better known to be more related to systemic inflammation than subcutaneous fat in other diseases.…”
Section: Discussionmentioning
confidence: 66%
“… 34 It was proposed that leptin which is one of the best-known systemically secreted adipokines would affect proliferation and survival of eosinophils and promote airway inflammation in several reports. 35 36 37 Considering that there were reports describing airway inflammation in asthma could be demonstrated as bronchial wall thickening on CT, 38 39 the positive association of SFA with WA or TA shown in this study might suggest that subcutaneous fat tissue may influence the airway inflammation through systemically secreted adipokines. These results were unexpected because visceral fat was better known to be more related to systemic inflammation than subcutaneous fat in other diseases.…”
Section: Discussionmentioning
confidence: 66%
“…Air trapping was seen in all cases. Interestingly, bronchial wall thickening, a finding commonly associated with the diagnosis of asthma (13), was seen in all patients of the SA and SA-AID groups, in 7 out of 9 of patients with SA-AG, but only in 3 out of 6 of the SA-AG-AID patients. No bronchiectasis was seen in the SA-AG-AID group.…”
Section: Resultsmentioning
confidence: 92%
“…[2][3][4][5][6][7][8][9] Further research indicates that airway remodeling is related to the severity of the disease and may result in relatively irreversible narrowing of the airways. 10,11 Many studies have assessed the structural changes that occur in asthma by using high-resolution computed tomography (CT), [12][13][14][15][16][17] in which airway-dimension indices, such as the luminal area, wall area, and wall area percentage, of a selected segmental bronchus are measured by using manual or automated techniques. Some of these studies demonstrated that the airway walls of subjects with asthma are thicker than those of healthy subjects and that airway wall thickening is related to air-flow obstruction and disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies demonstrated that the airway walls of subjects with asthma are thicker than those of healthy subjects and that airway wall thickening is related to air-flow obstruction and disease severity. [12][13][14][15][16][17] However, in previous studies, [12][13][14][15][16][17] one measurement point that was selected in a bronchus for analysis does not reflect the range and the variation trends of structural changes in airways of patients with asthma.…”
Section: Introductionmentioning
confidence: 99%